Dystonia‐Causing Mutations as a Contribution to the Etiology of Spasmodic Dysphonia. (22nd July 2016) - de Gusmão, Claudio M.; Fuchs, Tania; Moses, Andrew; Multhaupt‐Buell, Trisha; Song, Phillip C.; Ozelius, Laurie J.; Franco, Ramon A.; Sharma, Nutan
Abstract : Objective: Spasmodic dysphonia is a focal dystonia of the larynx with heterogeneous manifestations and association with familial risk factors. There are scarce data to allow precise understanding of etiology and pathophysiology. Screening for dystonia‐causing genetic mutations has the potential to allow accurate diagnosis, inform about genotype‐phenotype correlations, and allow a better understanding of mechanisms of disease. Study Design: Cross‐sectional study. Setting: Tertiary academic medical center. Subjects and Methods: We enrolled patients presenting with spasmodic dysphonia to the voice clinic of our academic medical center. Data included demographics, clinical features, family history, and treatments administered. The following genes with disease‐causing mutations previously associated with spasmodic dysphonia were screened: TOR1A (DYT1), TUBB4 (DYT4), and THAP1 (DYT6). Results: Eighty‐six patients were recruited, comprising 77% females and 23% males. A definite family history of neurologic disorder was present in 15% (13 of 86). Average age (± standard deviation) of symptom onset was 42.1 ± 15.7 years. Most (99%; 85 of 86) were treated with botulinum toxin, and 12% (11 of 86) received oral medications. Genetic screening was negative in all patients for the GAG deletion in TOR1A (DYT1) and in the 5 exons currently associated with disease‐causing mutations in TUBB4 (DYT4). Two patients tested positive for novel/rare variants in THAP1 (DYT6). Conclusion: Genetic screening targeted at currently known disease‐causing mutations in TOR1A, THAP1, and TUBB4 appears to have low diagnostic yield in sporadic spasmodic dysphonia. In our cohort, only 2 patients tested positive for novel/rare variants in THAP1 . Clinicians should make use of genetic testing judiciously and in cost‐effective ways.